Diet composition and feeding strategy of crosbanded barb, Puntioplites bulu (Bleeker, 1851) from Perak, Peninsular Malaysia - A. Ghani, Intan Faraha; Arshad, Aziz; Harmin, Sharr Azni; Christianus, Annie; Ismail, Muhammad Fadhil Syukri (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Diet composition and feeding strategy of crossbanded barb, Puntioplites bulu caught from Perak, Malaysia from October 2015 to October 2016 were studied in relation to size and stages. Based on the stomach contents of 256 individuals with total length of 13.5 to 37.5 cm, 5.47% were empty. Puntioplites bulu showed omnivorous feeding habits. Fed mostly on benthic plant materials (mostly algae) and aquatic invertebrate. Diet of P. bulu were primarily comprised of Bacillariophyceae, Chlorophyceae, crustacea, mollusca and plant matter. Estimation based on Schoener’s index showed high overlap dietary items between juvenile and adult stages, however ontogenetic shifts in diet were observed between these two stages. Adult P. bulu fed on varieties of items in prey size range whereas juveniles on smaller items. The stage based diet variances suggest that mouth gape and swimming ability may influence on the feeding habits of P. bulu. Description of dietary items and feeding strategy can offer an insight for proper management of this species particularly for aquaculture and conservation purposes.